Proceedings of the enviBUILD 2019. Buildings and Environment - Jozef, Hraška (De Gruyter, 2020)
The enviBUILD conferences are organized annually by one of the Central European universities. They are building on the legacy of the Buildings and Environment Conferences held by the Faculty of Civil Engineering of the Slovak Technical University. Since 2012 they have been carried out under the "enviBUILD" brand name. An overview of all previous conferences can be found at "www.cab.sk/pastevents.html". The enviBUILD conferences seek to map the current situation in the field of sustainable construction in the Central European region. The fourteenth sequel organized 2019 in Bratislava, as a one-day event, focused on building physics and applied technology in architecture, building construction and environmental engineering, with the following themes and topics: Indoor Environment and its Hygienic Aspects Sustainable Buildings and Environmental Assessment Building Materials and Components Energy Performance of Buildings Hygrothermal Performance of Buildings Responsive and Adaptive Building Envelopes Ventilation of Buildings Daylighting Building Acoustic Energy and Indoor Environmental Simulation Of the seventy abstracts submitted, some fifty valuable scientific articles were produced, most of which were presented directly at the conference. The contributions came from eight countries and more than a dozen academic institutions. All published papers were peer-reviewed by at least two independent professionals. In this way they provide a relatively comprehensive overview of the research and development in the field of sustainable construction, especially in Slovakia and the Czech Republic, enriched with inspirations from Austria, France, Hungary and Ukraine.